The Time Local Convex Hull method as a tool for assessing responses of fauna to habitat restoration: A case study using the perentie (Varanus giganteus: Reptilia: Varanidae) - Cross, Sophie; Tomlinson, Sean; Craig, M.D.; Bateman, Bill (CSIRO PUBLISHING, 2019)
Understanding the behavioural responses of animals to habitat change is vital to their conservation in landscapes undergoing restoration. Studies of animal responses to habitat restoration typically assess species presence/absencehowever, such studies may be restricted in their ability to show whether restoration is facilitating the return of self-sustaining and functional fauna populations. We present a case study using VHF/GPS tracking of a young adult perentie (Varanus giganteus), to demonstrate the range of applications of the Time Local Convex Hull method of home-range construction in analysing the behavioural responses of fauna to habitat change and restoration. Presence/absence studies provide single point locations of an animal, and the Minimum Convex Polygon method provides an invariant estimate of habitat use across the whole home range. However, the Time Local Convex Hull method provides a useful method for assessing movement and behavioural responses of fauna to habitat change and restoration, and the specific habitat requirements for the long-term support of populations. The breadth and multidimensionality of data generated indicates strongly that understanding the complex interactions between animals and their environment is fundamental to their conservation in the face of ever-increasing rates of human-induced habitat change and degradation.